Indonesia's Land Bank Authority: Aligning with Agrarian Law or Facilitating Land Grabbing? - Alimuddin, Nur Hidayani; Ayu Widowati, Dyah; Eka Mayasari, Riezka; Febrisari, Rizki; Jusafri, Jusafri (Universitas Negeri Semarang, 2024)
This research critically examines Indonesia's land bank regulations, introduced under the Job Creation Law to boost investment, but which risk promoting land grabbing, particularly affecting farming and indigenous communities. The study's novelty lies in its focus on assessing the compatibility of land bank policies with Indonesia's agrarian legal framework through the lens of legal utilitarianism. By employing normative research methods, including theoretical and regulatory analysis, the study identifies significant legal flaws in both the legislative process and the content of the regulations. These issues undermine the principles of agrarian justice, particularly in ensuring equitable land ownership rights. This research offers urgent recommendations to policymakers, advocating for the protection of vulnerable communities from the adverse effects of land bank policies.